Reliability and Quality of Complex Systems - O.V. Prokofiev (Надежность и качество сложных систем)
Background. Much research on artificial intelligence (AI) since its inception has been devoted to exploring a variety of problems and approaches for autonomous operation in application areas related to human health and life. The article is devoted to describing the origin of risks, systematizing the ways they manifest themselves in order to build systems for responsible purposes. Materials and methods. Since research in this area is not yet based on extensive implementation experience, the sources of risks discussed are a generalization of expert assessments of authoritative developers and are given as an example of autonomous weapons systems. Results. The main sources of risks and the trajectories of their development for various variants of cause-and-effect transformation have been identified. Conclusions. Directions for improving the processes of testing and debugging autonomous systems for critical purposes are formulated from the point of view of development and formation of application risks.